Childbearing intention and its associated factors: A systematic review. Issue 5 (11th March 2021) - Hashemzadeh, Mozhgan; Shariati, Mohammad; Mohammad Nazari, Ali; Keramat, Afsaneh
Abstract: Aim: This study aimed to provide comprehensive information about the core determinants of fertility intentions. Design: Systematic review. Methods: Ovid, MEDLINE, EMBASE, PsycINFO, CINAHL, Web of Science, SCOPUS and GOOGLE SCHOLAR were searched for the relevant articles published from 1946–December 2017. We updated our records by searching three computerized databases (Ovid MEDLINE, SCOPUS and WOS) from 2018–January 2021. Results: 53 studies included in the qualitative synthesis. The results of some studies indicated the impact of demographic factors, physical and psychological health, happiness and child desire. The most frequent variables in a couple's mesosystem were marital status, parity, partnership satisfaction and gender role attitude. The mesosystem of childbearing intention also included family and peers network. The EXEO system of the ECSM includes certain variables, such as job characteristics, urban residence, housing condition. The macrosystem comprises cultural and societal principles with broader influences on the couple's system.